Development and Validation of the Self-Stigma Scale for Secondary Vocational Students (SSS-SVS) - Leng J; Cai H; Liu F; Shi X; Fan Z (Psychology Research and Behavior Management)
Jiaqi Leng,1 Huilin Cai,1 Fei Liu,2 Xiaoli Shi,3 Zhiguang Fan4 1School of English, Jilin International Studies University, Changchun, 130117, People’s Republic of China; 2Section of Student Affair, ChangChun Vocational School of Technology, Changchun, 130117, People’s Republic of China; 3Department of Psychology, University of Exeter, Exeter, EX4 4 QG, UK; 4Department of Psychology, Shaoxing University, Shaoxing, 312000, People’s Republic of ChinaCorrespondence: Zhiguang Fan, Department of Psychology, Shaoxing University, Shaoxing, 312000, People’s Republic of China, Tel +86-0431-84924101, Fax +86 1 594-831-4623, Email fanyqm@126.comBackground: Stigma can not only threaten the self-identity of secondary vocational students, but also have negative effects on their mental health and behavior.Objective: This study aimed to develop the Self-Stigma Scale for Secondary Vocational Students (SSS-SVS) and test its reliability and validity.Patients and Methods: This study formed a scale based on the stigma conceptualization model and open questionnaire. The formal survey was divided into two stages. In the first stage, a preliminary questionnaire was administered to 328 secondary vocational students to develop a formal SSS-SVS according to the results of the data check. In the second stage, the SSS-SVS, Social Recognition of Secondary Vocational Students (SR-SVS), Intensity of Willingness to Become a Secondary Vocational Student (IWB-SVS), Stigma-Consciousness Scale (SCS), Learning Adjustment Scale (LAS), Professional Identity Scale for Secondary Vocational Students (PIS-SVS), and the Self-Compassion Scale (SCoS) were administered to 1079 vocational secondary school students.Results: The SSS-SVS consisted of 21 items which were divided into three dimensions of negative characteristics, self-deprecation, and opportunity loss, reflecting secondary vocational students’ perception of negative public evaluation, self-feeling under the influence of stigma, and cognition of negative impact on their identity. The confirmatory factor analysis (CFA) shows that the three-factor model has good fit indices. The total score and the scores of each dimension of the SSS-SVS were significantly and positively correlated with Stigma Consciousness; they were significantly and negatively correlated with SA-SVS, IDB-SVS, SVS-PIS, Learning Adjustment, and Self-Compassion. Both the Cronbach’s α coefficients of the total scale and each dimension and the McDonald’s ω coefficients were satisfactory. Additionally, the scale had measurement equivalence across gender and grade levels. The SSS-SVS has limitations and may be affected by cultural background. Future studies should expand the sample and conduct cross-cultural verification.Conclusion: The SSS-SVS is a reliable and valid instrument for assessing secondary vocational students’ self-stigma, providing support for developing relevant programs and policies. It also advances secondary vocational education and enhances students’ mental health.Keywords: secondary vocational students, self-stigma, reliability, validity